Acting Styles, Nuances and Linguistic Aesthetics: A Case Study of Ibrahim Chatta in Yoruba Films - Adejoke Adetoun Fadirepo; Adeyemi Oluwadamilare Oresanya (Yoruba Studies Review)
Acting style is the artistic feature and ingenuity of the actor exhibited over a long period of time acting in films. It is the attainment and acquisition of skills, ingenious and professional creativity, exhibited by the actor in the process of carrying out a role in film or play production. Acting style can be inferred to be individualistic. In Yoruba films, there is a crop of non-native actors who are fluent in the language of their nativity as well as being conversational in the Yoruba language movies which aid their celebrity status. The inability to acculturate to the expected character through diction, gesticulation and socio-linguistic nuances create disorientation between the actors and the audience. This study is hinged on Whorpian Theory on language which posits that the individual perceives his or her environment through the process of thought which is influenced by the language he uses. The method of research is content analytical. Film content is analyzed to raise awareness on the style, nuances linguistic aesthetics of Ibrahim Chattah in selected films. Our findings show that producers and casting directors are the culprit of this deficiency, due to their sense of profit making by using casts with celebrity status in order to increase their profit margin at the show room. This study thereby concludes that directors, producers and casting directors should be more creative by developing a sense of professionalism, making preference for quality over quantity in the Yoruba films. This research recommends adequate training for all actors, especially multilingual ones to increase their versatility, develop skill and technique in order to sustain them and increase their market value in the industry.